2021
DOI: 10.1182/blood-2021-147744
|View full text |Cite
|
Sign up to set email alerts
|

Tasquinimod Targets Immunosuppressive Myeloid Cells, Increases Osteogenesis and Has Direct Anti-Myeloma Effects By Inhibiting c-Myc Expression in Vitro and In Vivo

Abstract: Introduction Immunotherapy has revolutionized cancer treatment and significantly affected the management of Multiple Myeloma (MM) patients. Unfortunately, these immunotherapeutic approaches are hampered by the presence of a suppressive bone marrow microenvironment including myeloid derived suppressor cells and tumor associated macrophages. Tasquinimod (TasQ), an immunomodulatory compound, is currently in phase Ib/IIa for relapsed/refractory MM patients (NCT04405167). TasQ blocks the interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recently, we also investigated the effects of S100A9 inhibitor tasquinimod, currently evaluated in clinical trial for relapsed/refractory MM patients and observed a clear reduction in the M-MDSC subset in vivo (NCT04405167). In addition, tasquinimod abolished the immunosuppressive activity of in vitro generated MDSC, illustrating its potential as an immunotherapeutic compound ( 82 ).…”
Section: Therapeutic Approaches To Target Mdsc In Hematological Cancersmentioning
confidence: 99%
“…Recently, we also investigated the effects of S100A9 inhibitor tasquinimod, currently evaluated in clinical trial for relapsed/refractory MM patients and observed a clear reduction in the M-MDSC subset in vivo (NCT04405167). In addition, tasquinimod abolished the immunosuppressive activity of in vitro generated MDSC, illustrating its potential as an immunotherapeutic compound ( 82 ).…”
Section: Therapeutic Approaches To Target Mdsc In Hematological Cancersmentioning
confidence: 99%